ANALISIS FUNGSI KOTOWAZA YANG TERBENTUK DARI KATA TORA (?) SERTA PADANANNYA DALAM PERIBAHASA BAHASA INDONESIA - Rahmi Febrianti; Nova Yulia (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
Japanese proverbs (kotowaza) are words that have been used by people since ancient times and contain meanings such as lessons or satire. Idiomatic phrases consist of two or more words that have specific meanings. Many Japanese proverbs use metaphors or comparisons, and one commonly used subject is tora (?), the tiger. Kotowaza is a form of language that is difficult to learn and understand, often leading to misunderstandings in capturing the implied meaning, especially for foreigners learning Japanese. This research aims to understand the function of kotowaza containing the word tora (?) on the Kotowaza Daijiten website and the Obunsha Standard Proverbs Dictionary. The data in this study are kotowaza related to the word tiger found on these websites. The research method used is qualitative research. The data collection technique used in this study is the literature review technique. Based on the research results, 24 instances of kotowaza were found across 4 functions: 7 instances of kougekiteki kotowaza, 9 instances of keikenteki kotowaza, 8 instances of kyoukunteki kotowaza, and no instances of yuugiteki kotowaza.